MOLTING AND SPAWNING SYNCHRONY IN Marsupenaeus japonicus FROM TOKYO BAY - Agung Setiarto (JOURNAL OF COASTAL DEVELOPMENT, 2006)
This study was the first attempt to examine the molt stage and molting cycle in relation to the ovarian development of M japonicus in Tokyo Bay In particular the study was done to reveal molting and spawning relationship, to predict reproductive peaks and thus larval recruitment and to investigate the possibility of multiple spawning within one molt cycle in natural condition, Ohh: three out of five stages were represented in the samples since the early premalt (A) and ecdysis (E) occured in a very short time. There occured was a co-occurrence between ovarian maturation and molt stage, in which maturing ovaries occurred at B (late postmolt) to D, (earlv premolt) stage, mature ovaries at C (intermold to D; (late premoly, and spent ovaries at D, to D,. Molting and spawning synchronization was observed in kuruma prawn, in which molting fequency was highest prior to and at the end of spawning season. There was a possibility of multiple spawning within single molt cycle in wild kuruma prawn, since there were enough time for spent ovaries to redevelop into mature ones.